G156(P) Effectiveness of a nurse and pharmacist led hepatitis C virus treatment pathway in a paediatric setting. (May 2019) - Price, V; Marra, F; Doherty, C; Hague, R
Abstract : The aim is to measure the effectiveness of a novel clinical nurse specialist (CNS) and blood borne virus (BBV) pharmacist led hepatitis C virus (HCV) treatment pathway in a paediatric setting. The most common mode of acquisition of HCV in children is mother to child transmission (MTCT) during the perinatal period with genotype 1 and genotype 3 the most common genotypes seen in this paediatric setting. Treatment for HCV has evolved rapidly with the advent of direct acting antiviral (DAA) and has transformed the therapeutic landscape providing a cure in over 90% of cases. The availability of DAA's licenced for use in patients aged 12–18 years has extended these treatment options the paediatric setting. Nine young people 12–18 years with HCV infection attending a paediatric setting were offered treatment following the CNS and BBV pharmacist led treatment pathway. Eight had aquired HCV by mother to child transmission in one young person the mode of transmission was unclear. Eight young people had HCV genotype 1 and one young person had HCV genotype 3 The pathway incorporates a pre-treatment assessment of blood tests fibroscan and counselling carried out by the CNS and BBV pharmacist. During treament telephone follow up and home visit if required. End of treatment blood test and counselling and follow up 12 weeks after treatment ends to determine if a sustained viral response (SVR) has been achieved. Fibroscan measures the level of liver fibrosis in HCV infection, it is a non invasive alternative to liver biopsy and provides a score on which to base DAA duration. Nine young people had a score of F1- F2kpa. Fibroscan requires a skilled operator it is offered by the CNS in this paediatric setting and is the only paediatric trained operator in the region. Eight young people with HCV genotype 1 were treated with 8 weeks Harvoni and one young person with HCV genotype 3 was treated with 8 weeks Epclusa. Six young people had an undetected hepatitis C virus at end of treatment (2 are mid treatment). One young person had an SVR at 12 weeks post treatment, one failed to attend for SVR 12. Seven young people are still within 12 weeks of treatment end. A CNS and BBV pharmacist led HCV treatment pathway in the paediatric setting is a safe and effective and encourages engagement.